Hubungan aktivitas fisik dan obesitas sentral dengan hiperglikemia wanita dewasa: Cross-sectional study - Bohari Bohari; Nuryani Nuryani; Rukman Abdullah; Lili Amaliah; Fahmi Hafid (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Women in Indonesia are a group at risk of experiencing high blood glucose levels with increasing age. The purpose of the study was to analyze the relationship between physical activity and central obesity on hyperglycemia in adult women. The type of research is quantitative with a cross-sectional design on adult women at the Telaga Biru Public Health Center, Gorontalo Regency in 2019. The sample size is 248 people using purposive sampling. The method of collecting physical activity data is measured using a Physical Activity Level (PAL) questionnaire, central obesity is measuring waist circumference, and current blood glucose levels for hyperglycemic status. The statistical test is the chi-square test with 95% CI. The results showed that physical activity included in the light category was very high at 91.1% and central obesity status was also high at 61,3%. The results of current blood glucose levels showed that respondents who experienced hyperglycemia were low at only 15,3%. Physical activity had no significant association with hyperglycemia (p= 0,142), central obesity had a significant association with hyperglycemia (p= 0,005). The conclusion is that central obesity has a significant relationship with the incidence of hyperglycemia in adult women with an OR value of 3,52